2006
DOI: 10.5034/inquiryjrnl_43.3.195
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Elder Care on Women's Labor Supply

Abstract: Adult daughters traditionally have served as primary caregivers for frail unmarried adults, but the levels of care they have provided in the past may interfere with their growing work responsibilities. This paper examines the impact of time transfers to elderly parents on labor supply at midlife. Using a sample of women ages 55 to 67 in the Health and Retirement Study, we estimate panel data models of annual hours of paid work controlling for the endogeneity of time assistance to parents. The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 34 publications
3
83
0
2
Order By: Relevance
“…3, JUNE 2009 www.ccnonline.org or eliminates access to employer-sponsored retirement accounts, limits contributions to participatory pension plans, and limits or eliminates saving for emergencies or other retirement needs. 26 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3, JUNE 2009 www.ccnonline.org or eliminates access to employer-sponsored retirement accounts, limits contributions to participatory pension plans, and limits or eliminates saving for emergencies or other retirement needs. 26 …”
mentioning
confidence: 99%
“…For middle-aged women, caregiving reduces paid work hours by abut 41%. 26 Reduced Benefits. Fifteen percent of family caregivers quit their jobs or reduced the number of their work hours because of the need to provide care, thereby also reducing their salary and paid benefits, including retirement and health insurance.…”
mentioning
confidence: 99%
“…There are few variables that predict household structure but have no direct effect on labor supply. Past scholars have asserted that the adult's number of siblings might predict co-residence with a disabled senior parent or in-law but could be excluded from directly predicting her labor supply (Johnson and Lo Sasso 2006). Similarly, the adult's number of own children has been held to predict labor supply, but not co-residence with a disabled senior (Johnson and Lo Sasso 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Past scholars have asserted that the adult's number of siblings might predict co-residence with a disabled senior parent or in-law but could be excluded from directly predicting her labor supply (Johnson and Lo Sasso 2006). Similarly, the adult's number of own children has been held to predict labor supply, but not co-residence with a disabled senior (Johnson and Lo Sasso 2006). We explored these options, but found that, based on the F-test, neither the birth order of the husband nor husband's number of siblings was a strong enough predictor of mother-in-law co-residence to serve as an instrument.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation